Phase transitions in the coal-water-methane system - Alexeev, A.D.; Ulyanova, E.V.; Kalugina, N.A.; Degtyar, S.E. (Condensed Matter Physics, 2006)
Low temperature phase transitions in water and methane occurring in fossil coals were studied experimentally using Nuclear Magnetic Resonance (NMR) techniques. Contributions of constituent fluids into narrow line of ¹H NMR wide line spectrum were analyzed.